Religiosity, Spirituality, Forgiveness, Religious Coping as Predictors of Life Satisfaction and Generalized Anxiety: A Quantitative Study on Turkish Muslim University Students - Ali Ayten; Sema Karagöz (Spiritual Psychology and Counseling)
During the last two decades, several studies have been carried out to examine the main predictors of life satisfaction and anxiety. This paper investigates the connection between spirituality, religiosity, religious coping, forgiveness, anxiety, and satisfaction with life in the case of a Turkish Muslim sample. In total 560 respondents were selected from different faculties of Bolu Abant İzzet Baysal University. 53.4% (N= 299) of the sample were females and 46.6% (N= 261) of them were males. Participants’ age changed to between 18 and 38 years. 28.4% (N=159) of students were from faculty of education, 25.9% (N=145) of students were from faculty of architecture and engineering, 23.8% (N=133) of students were from faculty of theology, and 22% (N=123) of students were from faculty of administrative sciences and economics. In the present researchers utilised the “Forgiveness Scale”, “Positive Religious Coping Scale”, “Religious Struggles”, “Scale for Satisfaction with Life” and “Generalised Anxiety Scale” to collect data. According to multiple regression findings, religiosity and forgiveness were significant predictors for life satisfaction. Moreover, forgiveness and religious coping (religious struggles and positive religious coping) were significant predictors of generalized anxiety.